1998
DOI: 10.1897/1551-5028(1998)017<0377:iofaat>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF FLUOROQUINOLONE ANTIBIOTICS AS THE MAIN SOURCE OF umuC GENOTOXICITY IN NATIVE HOSPITAL WASTEWATER

Abstract: Abstract-Previous work revealed genotoxic effects in the wastewater of a large university hospital using a bacterial short-term genotoxicity assay, based on a umuC::lacZ fusion gene (umuC assay). These studies ruled out disinfectants and detergents as main causative agents of the genotoxic effects. This paper focuses on specific hospital-related drugs as the cause. The ratio of theoretical mean wastewater concentrations (derived from consumption data) and lowest observable effect concentrations of selected pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 24 publications
(31 reference statements)
1
106
1
3
Order By: Relevance
“…Several DNAdamaging agents, such as fluoroquinolone (FQ) antibiotics and nitroarenes, were identified as major mutagens in waters by combination of the SOS/umu test as a genotoxicity bioassay and HPLC as a fractionation method. Hartmann et al [19] used HPLC coupled with fluorescence detection to quantify fluoroquinolone antibiotics, and found one major DNA-damaging agent (ciprofloxacin) in the wastewater of a hospital in Switzerland. Ma et al [12] used S. typhimurium strain TA1535/pSK100 and the O-acetyltransferaseoverexpressing strain NM 2009 in different fractions of river waters in the Jialu River basin, China, and found that flumequine and a MN ratio significantly increased compared with concurrent solvent control (one-way ANOVA, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several DNAdamaging agents, such as fluoroquinolone (FQ) antibiotics and nitroarenes, were identified as major mutagens in waters by combination of the SOS/umu test as a genotoxicity bioassay and HPLC as a fractionation method. Hartmann et al [19] used HPLC coupled with fluorescence detection to quantify fluoroquinolone antibiotics, and found one major DNA-damaging agent (ciprofloxacin) in the wastewater of a hospital in Switzerland. Ma et al [12] used S. typhimurium strain TA1535/pSK100 and the O-acetyltransferaseoverexpressing strain NM 2009 in different fractions of river waters in the Jialu River basin, China, and found that flumequine and a MN ratio significantly increased compared with concurrent solvent control (one-way ANOVA, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A causal relationship has been established between genotoxic effects and potential genotoxicants in native hospital wastewater [19] and ground waters [12]. However, due to the existence of various chemical contaminants at low concentrations in source waters and the lack of data on genotoxicity of many pollutants, identifying the chemical responsible for genotoxicity is not an easy task with respect to source waters.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the cyanobacterium (Microcystis aeruginosa) and duckweed (Lemna minor) were quite sensitive to fluoroquinolones, the median effective concentrations (EC 50 ) of levofloxacin for 5-d growth reproduction of M. aeruginosa and 7-d reproduction of L. minor were 7.9 and 51 lg/L, respectively (Robinson et al, 2005;Ebert et al, 2011). Most of quinolones exhibited mutagenicity to bacteria (Mamber et al, 1993), and a large proportion of hospital sewages containing quinolone-like antibiotics induced bacterial genotoxicity (Hartmann et al, 1998). In addition, it was reported that more than 70% of bacteria had become insensitive against at least one antibiotic and exhibited multiple resistance patterns (Hirsch et al, 1999), and the antibiotic resistance of bacteria has become a serious issue.…”
Section: Introductionmentioning
confidence: 99%
“…For example, eight quinolones were the prominent contaminants in sediments and aquatic plants of the Baiyangdian Lake, China, with the concentrations of 65.5-1166 and 8.37-6532 μg/kg, respectively . Ciprofloxacin, one of the most commercial quinolones, was found in Switzerland hospital effluents as high as 89 μg/L (Hartmann et al, 1998). It was reported that ciprofloxacin and enrofloxacin were not readily biodegradable by sewage sludge organism (Ebert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al (2007) investigated genotoxicity potential of 20 quinolones by umuC bioassay; the result indicated that all the tested compounds showed high toxicity with 10% of the maximum response concentration (EC 10 ) ranged from 0.61 to 2917 nmol/L. In addition, it was reported that genotoxicity in the wastewater of the hospital was mainly caused by quinolone antibiotics (Hartmann et al, 1998). The removal of those compounds in sewage treatment plants is a complex issue, and their toxicity patterns are flexible under various treatment processes, such as ozonation, UV photolysis and chlorination disinfection.…”
Section: Introductionmentioning
confidence: 99%